PENGARUH REKRUTMEN DAN PENEMPATAN KERJA KARYAWAN TERHADAP PRESTASI KERJA KARYAWAN PADA PT MASMEDIA BUANA PUSTAKA CABANG ACEH - Zenitha Maulida; Fahada Elvina; Nurbismi Nurbismi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2023)
The purpose of this study was to determine the effect of recruitment and placement of employees on employee performance at PT Masmedia Buana Pustaka Aceh Branch, both partially and simultaneously, that the recruitment and placement of employees was less than optimal and stable in the recruitment and placement of employees. This research method is a quantitative method, with the number of samples in this study were 72 respondents. Research data was collected through questionnaires distributed to respondents. The research data were analyzed using multiple linear regression models and processed using SPSS (Statistical Package For The Social Sciences). Hypothesis testing using multiple linear regression analysis with the F test and t test meant to determine simultaneously and partially the effect of variables independent of the dependent variable at the 95% confidence level (α=0.05). The results in this study based on simultaneous tests show that the variables of recruitment and job placement of employees have a significant effect on the performance of employees of PT Masmedia Buana Pustaka Aceh Branch. The partial test also shows that the recruitment variable has a significant effect on employee performance at PT Masmedia Buana Pustaka Aceh Branch. Then employee work placement has a significant effect on employee performance at PT Masmedia Buana Pustaka Aceh Branch.